cardiorespiratory fitness is associated with hard and light intensity physical activity but not time spent sedentary in 10-14 year old schoolchildren: the HAPPY study. - Sarah J Denton; Michael I Trenell; Thomas Plötz; Louise A Savory; Daniel P Bailey; Catherine J Kerr (PLoS ONE, 2013)
Sedentary behaviour is a major risk factor for developing chronic diseases and is associated with low cardiorespiratory fitness in adults. It remains unclear how sedentary behaviour and different physical activity subcomponents are related to cardiorespiratory fitness in children. The purpose of this study was to assess how sedentary behaviour and different physical activity subcomponents are associated with 10-14 year-old schoolchildren's cardiorespiratory fitness.135 schoolchildren (81 girls, 12±1 year) completed 7-day minute-by-minute habitual physical activity monitoring using triaxial accelerometers and undertook a maximal cardiorespiratory fitness test.After controlling for sex, age, ethnicity, socioeconomic status and total wear time, light physical activity (1.5-2.9 METs) was negatively associated (β = -.24, p<.01) and hard physical activity (≥9 METs) positively associated (β = .45, p<.001) with cardiorespiratory fitness. Vigorous and hard physical activity were associated with cardiorespiratory fitness for boys (F = 5.64, p<.01) whereas light, moderate and hard physical activity were associated with physical fitness for girls (F = 10.23, p<.001). No association was found between sedentary time and cardiorespiratory fitness (r = -.13, p>.05). Sedentary to active transitions revealed little variability between cardiorespiratory fitness tertiles.Hard physical activity (≥9 METs) holds greater potential for cardiorespiratory fitness compared to physical activity of lower intensities. There was no relationship between sedentary behaviour and cardiorespiratory fitness. These findings suggest that, for children, advice should focus on higher intensity physical activity and not sedentary behaviour as a means to maintain or improve cardiorespiratory fitness. Future research should explore longitudinal relationships between hard physical activity, cardiorespiratory fitness and health parameters.